2011
DOI: 10.1002/cpp.737
|View full text |Cite
|
Sign up to set email alerts
|

Early Maladaptive Schema Factors, Chronic Pain and Depressiveness: a Study with 271 Chronic Pain Patients and 331 Control Participants

Abstract: Chronic pain and depression are coexisting entities with high simultaneous prevalence. Both are linked with early adversities. Early maladaptive schemas (EMS) can be seen as a reflection of these adversities. EMSs extensively indicate underlying psychic patterns and provide a good opportunity to detect covert processes and psychic shapes (latent factors), which create the basis of how people rate their schemas. The purpose of this study was to explore these latent, higher order schema factors (SF) and to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…There are also associations between increased perceived stress and chronic pain (van Uum et al, 2008) as well as major depression (Staufenbiel, Penninx, Spijker, Elzinga, & van Rossum, 2013). Saariaho, Saariaho, Karila, and Joukamaa (2012) found a "pain predisposing and maintaining factor" that comprised the schemas "unrelenting standards" and "self-sacrifice" in their study on chronic pain patients. Self-sacrificing behaviour in somatoform patients may be associated with experiences of role reversal during childhood, which is known as parentification.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There are also associations between increased perceived stress and chronic pain (van Uum et al, 2008) as well as major depression (Staufenbiel, Penninx, Spijker, Elzinga, & van Rossum, 2013). Saariaho, Saariaho, Karila, and Joukamaa (2012) found a "pain predisposing and maintaining factor" that comprised the schemas "unrelenting standards" and "self-sacrifice" in their study on chronic pain patients. Self-sacrificing behaviour in somatoform patients may be associated with experiences of role reversal during childhood, which is known as parentification.…”
Section: Discussionmentioning
confidence: 97%
“…The highest performance expectations in combination with a high willingness to put one's own needs aside, as expressed in a self-sacrificing behaviour style, seem to be characteristic for patients with somatoform disorders. Saariaho, Saariaho, Karila, and Joukamaa (2012) found a "pain predisposing and maintaining factor" that comprised the schemas "unrelenting standards" and "self-sacrifice" in their study on chronic pain patients. Studies on fibromyalgia have shown that a perfectionistic and self-sacrificing lifestyle plays a crucial role in the development and persistence of fibromyalgia (Kivimaki et al, 2004;van Houdenhove, Neerinckx, Onghena, Lysens, & Vertommen, 2001;Wentz, Lindberg, & Hallberg, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Because this model defined domains for only 15 schemas, the remaining three first‐order schema factors were allowed to freely correlate with each other and the second‐order domains. A two‐domain and a three‐domain model based on samples of adults with and without chronic pain were also fitted (Saariaho, Saariaho, Karila, & Joukamaa, ), as well as a model with a single global domain. Finally, bifactor models with and without correlations between the first‐order schema factors were examined.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic pain disorder (CPD; comorbidity 3.7% [6]) fulfils this condition. Although there is a lack of comparisons between different Axis I disorders, a study on EMS in OCD versus healthy controls does exist [8], as well as comparisons of ED [9] and CPD [10] samples with controls. These studies found higher levels of EMS in clinical samples.…”
Section: Introductionmentioning
confidence: 99%